Vpliv terapije z lutko na življenje oseb, obolelih za demenco - Mlinar Reljić, Nataša (Obzornik zdravstvene nege, 2019)
Introduction: Doll therapy is a non-pharmacological approach in managing patients who suffer from dementia that reduces spiritual and emotional distress and agitation, and improves communication. The purpose of the systematic literature review was to present psychological, social and spiritual effects of doll therapy on people with dementia. Methods: A systematic literature review was used. The search was conducted in databases CINAHL, Science Direct and PubMed. Original scientific articles published since 2001 were included. Scientific articles with inadequate content or population, review articles and articles in languages that were not in English were excluded. The following search keywords were used: 'doll therapy', 'doll', 'dementia', 'spiritual', 'psychological', 'social', 'aspect' and 'nursing'. From a total of 135 results, 10 articles were included in the final analysis. Data was analyzed using the content analysis method. Results: Three content categories were developed: (1) Connection; (2) Social contacts; (3) Well-being and comfort. The results show the importance of connection and social contact, and highlight the need for wellbeing. These are important psychosocial and spiritual aspects of people with dementia. Discussion and conclusion: We have found that doll therapy in nursing people with dementia is an effective and useful approach that has a beneficial effect on their spiritual and emotional well-being. The approach encourages interaction of people with dementia with staff and with others. Therefore, from the viewpoint of providing psychosocial and spiritual care of people with dementia, the approach is appropriate and recommended.
Keywords: demenca; dementia; doll; lutka; medicinske sestre; nurses; nursing care; older people; starejše osebe; zaupanje; zdravstvena nega